- #1
hotjohn
- 71
- 1
Homework Statement
the correct solution is
∫ tan²x sec²x sec²x dx =
replace the first sec²x with (tan²x + 1):
∫ tan²x (tan²x + 1) sec²x dx =
expand it into:
∫ (tan^4x + tan²x) sec²x dx =
let tanx = u
differentiate both sides:
d(tanx) = du →
sec²x dx = du
substituting, you get:
∫ (tan^4x + tan²x) sec²x dx = ∫ (u^4 + u²) du =
break it up into:
∫ u^4 du + ∫ u² du =
[1/(4+1)] u^(4+1) + [1/(2+1)] u^(2+1) + c =
(1/5)u^5 + (1/3)u³ + c
(1/5)tan^5(x) + (1/3)tan³(x) + c
is it wrong to make in into ∫ tan²x ( (1 + tan²x )^2 ) dx
= ∫ tan²x ( 1 + 2tan²x + ((tanx)^4 ) ) dx ?
= (1/3)(tanx)^3 +(2/5)(tanx) ^5 + (1/7)(tan x ) ^7 ?